Late complications after a Yersinia enterocolitica epidemic: a follow up study. - Lindholm, H (1991)
Ninety four Finnish conscripts were affected by a Yersinia enterocolitica epidemic in 1973. Thirteen years later 75 men completed a questionnaire about their present health. One half had no health problems, and the most common complaints in the other subjects were musculoskeletal disorders. Sixteen men wanted to be re-examined. In three cases a chronic connective tissue disease was diagnosed. Two men had ankylosing spondylitis. The most notable results of this study were (a) the fairly low number of late complications, (b) the close correlation between complications and the HLA-B27 antigen, and (c) the correlation between raised yersinia antibody titres and the late complications. The nature of the primary causative agent may affect the development of late complications.